Faktor Pembentukan Kerjasama Politik Parti Islam Se-Malaysia (PAS) dengan parti politik di Malaysia dari 1974-2022 - Mohd Isa, Nur Ayuni; Ahmad, Zaid; Talib, Ahmad Tarmizi; Jawan, Jayum; Abdul Razak, Ratna Roshida (USIM Press, 2023)
Malaysia as a democratic country that practises a multi-party system; hence a single party could not gain most seats to form the government alone. This had led to the formation of political coalition by PAS. As of now, PAS had established seven political coalitions with different parties of policies and backgrounds, from Barisan Nasional (BN) to Harakah Keadilan Rakyat (HAK) to Angkatan Perpaduan Ummah (APU) to Barisan Alternatif (BA), Pakatan Rakyat (PR), Muafakat Nasional (MN) and lastly, Perikatan Nasional (PN), from 1974 until 2022. Therefore, the study aimed to explain the influences that involves in the formation of PAS's political coalitions. In this study, data were analysed qualitatively via in-depth interviews with PAS, PKR, UMNO, and DAP main leaders, and the extraction of the content analysis from the texts of Presidential Policy Speech delivered at the Annual Muktamar from 1974 to 2020. Findings have revealed that the political coalitions created by PAS were formed through discussions of common goals. Finding on the impact of political cooperation indicate that PAS has made three rational judgements based on 3 influences; i) forming a political coalition to achieve the policy objectives of the party (policy seeking) that occurred to their mission to implement Islamic Judiciary into the governance of the country, (ii) gaining power (office seeking), (iii) gaining votes to win elections (vote seeking). The study’s finding undoubtedly contributes to the richness of political sciences knowledge by analyzing the influence and factors made by political party in the act of forming political coalition.